2019
DOI: 10.1128/mbio.02614-19
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transposon Screen of a Pseudomonas syringae mexB Mutant Reveals the Substrates of Efflux Transporters

Abstract: Bacteria express numerous efflux transporters that confer resistance to diverse toxicants present in their environment. Due to a high level of functional redundancy of these transporters, it is difficult to identify those that are of most importance in conferring resistance to specific compounds. The resistance-nodulation-division (RND) protein family is one such example of redundant transporters that are widespread among Gram-negative bacteria. Within this family, the MexAB-OprM protein complex is highly expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…A randomly-barcoded mariner transposon library of P. syringae B728a described previously [13,14] was inoculated by vacuum infiltration into the leaves of the three plant species to identify genes contributing to host colonization. This mutant library contains 281,417 total strains having insertions mapped in the B728a genome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomly-barcoded mariner transposon library of P. syringae B728a described previously [13,14] was inoculated by vacuum infiltration into the leaves of the three plant species to identify genes contributing to host colonization. This mutant library contains 281,417 total strains having insertions mapped in the B728a genome.…”
Section: Resultsmentioning
confidence: 99%
“…RB-TnSeq is a powerful method that has been used in a variety of bacterial species to identify those genes that contribute to fitness in diverse in vitro conditions [11,14,15]. In one TnSeq study, about 100 genes were found to either increase or decrease the fitness of Dickeya dadantii in chicory [16], highlighting the importance of the biosynthetic pathways for leucine, cysteine, and lysine for bacterial growth within the plant.…”
Section: Discussionmentioning
confidence: 99%
“…RB-TnSeq is a powerful method that has been used in a variety of bacterial species to identify those genes that contribute to fitness in diverse in vitro conditions [12,15,19]. In one TnSeq study, about 100 genes were found to either increase or decrease the fitness of Dickeya dadantii in chicory [20], highlighting the importance of the biosynthetic pathways for leucine, cysteine, and lysine for bacterial growth within the plant.…”
Section: Discussionmentioning
confidence: 99%
“…A randomly-barcoded mariner transposon library of P. syringae B728a described previously [14,15] was inoculated by vacuum infiltration into the leaves of the three plant species to identify genes contributing to host colonization. This mutant library contains 281,417 total strains having insertions mapped in the B728a genome.…”
Section: Inoculation Of a Barcoded Transposon Library In Multiple Plamentioning
confidence: 99%
“…The efflux transporter MexAB-OprM may be required to tolerate the presence of these plant defense compounds as they accumulate to high levels in the apoplast. As different plant species produce different defensive compounds (Tegos et al 2002), despite its wide substrate range MexB is not capable of excluding all potential antimicrobial molecules (Helmann et al 2019). It is tempting to speculate, therefore, that those common bean varieties and other plant species in which strain B728a achieves the lowest population size and for which MexB was required for maximal growth produce inhibitory compounds and that these compounds are also substrates for MexB.…”
Section: Discussionmentioning
confidence: 99%